Pendampingan Legalitas Usaha Olahan Pangan KWT Rasa Saling Sayang Desa Kuta Lombok Tengah - Zuhdiyah Matienatul Iemaaniah; Lolita Endang Susilowati; Bambang Hari Kusumo; Sukartono; Andre Rachmat Scabra; Sitti Hilyana; Sadikin Amir; Heldy Sardianto (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Activities that can improve the community's economy can be carried out through the development of MSEs micro and small entreprises. This activity encourages the home industry to become increasingly developed. Kuta Village has become a Special Economic Zone that develops tourism activities. Tourism areas require food supplies for various activities carried out around the Mandalika Circuit. The development of processed home industrial food can later provide benefits to improve the community's economy. Service activities will be carried out for 6 months from July 2023 to December 2023 in Kuta Village with the target group KWT Rasa Saling Sayang which is a KWT assisted by the University of Mataram in 2022. Activities are carried out using socialization and participation methods by involving community participation in managing the legality of MSEs micro and small entreprises businesses so that obtain distribution permits on the market. The aim of this service activity is to help groups of women farmers to obtain the legality of home industrial food processing businesses. The results of this service activity include obtaining NIB, halal certificates for processed food products and also arranging PIRT MSEs KWT Rasa Saling Sayang